Variable selection in multivariate linear regression with random predictors - Mbina Mbina, Alban; Nkiet, Guy Martial; N’guessan, Assi (South African Statistical Journal, 2023)
We propose a method for variable selection in multivariate regression with random predictors. This method is based on a criterion that permits to reduce the variable selection problem to a problem of estimating a suitable set. Then, an estimator for this set is proposed and the resulting method for selecting variables is shown to be consistent. A simulation study that permits to study several properties of the proposed approach and to compare it with existing methods is given.